أثر إضافة الكومبوست المحضر من المنتجات الثانوية لشجرة الزيتون على بعض خواص التربة والإنتاج لمحصول الذرة الصفراء (Latakia University Journal -Biological Sciences Series, 2019)
تم تحضير الكومبوست من تفل الزيتون 70%, بقايا تقليم الزيتون 10%, تبن نجيليات 10% وسواد بلدي  أبقار 10% بالتخمير الهوائي مدة 14 أسبوع تم خلالها مراقبة درجة الحرارة والرطوبة وإجراء التقليب الدوري للخلطة، وإضافة مياه عصر الزيتون لتعديل درجة رطوبة الخلطة. أخذت عينات في بداية ونهاية مرحلة التخمير لإجراء التحاليل الكيميائية. أضيف الكومبوست الرطب إلى معاملات التجربة بمعدل 5 و10 كغ /م2 وبقي الشاهد بدون إضافة. دلت النتائج على تحسن خواص التربة الكيميائية، فقد زادت المادة العضوية بنسبة 150% و320.3%، الآزوت بنسبة 102.7% و187.7 %، الفوسفور بنسبة 15.6% و33.3% والبوتاسيوم بنسبة 35.1 % و52.5 % في المعاملات 5،10 كغ على التوالي بالمقارنة مع الشاهد، وانخفضت درجة الملوحةEC  ورقم الـ PH أيضاً، وكانت هناك زيادة في أعداد الكائنات الحية الدقيقة إذ كانت نسبة الزيادة في عدد البكتريا عن الشاهد 94%، 107%، والفطريات 160%، 152% في المعاملات 5،10 كغ على التوالي. وزاد الإنتاج الحبي في المعاملات المطبقة 8.2 طن، 8.9 طن في المعاملات 5،10 كغ على التوالي بالمقارنة مع الشاهد 7.1 طن وتحسنت مواصفات الإنتاج من حيث نسبة الزيت، البروتين والنشاء. Compost has been  prepared from olive pomace 70%, remnants of olive pruning 10%, straw10%, and cow manure 10% with aerobic fermentation during 14 weeks.  Temperature and humidity were controlled. Turning heap and adding olive mill wastewater to modify the  humidity was made periodically. Samples were taken from this mixture both at the beginning and at the end of the fermentation stage to make chemical analysis. A wet compost was added to the test trials with rate 5 and 10 kg /m2 in November every two years. The results showed improved chemical soil properties.  Organic matter has increased by 150 % and 320.3%, nitrogen by 102.7% and 187.7%, phosphorus 15.6% and 33.3 %, and potassium by 35.1% and 52.5% in applied trials of 5, 10 kg, respectively and in comparison with the control. The degree of salinity and PH became less. And there was an increase in the number of bacteria by 94% and107%, compared with the control, and in the number of fungi by160% and 152% in applied trials of 5, 10 kg, respectively. This has led to an increase in the production to 8.2 tons and 8.9 tons in trials of 5, 10 kg, respectively and in comparison with the control 7.1 tons, and to an improvement in the production characteristics.